2016
DOI: 10.1063/1.4945026
|View full text |Cite
|
Sign up to set email alerts
|

On the magnetic anisotropy and nuclear relaxivity effects of Co and Ni doping in iron oxide nanoparticles

Abstract: We report a systematic experimental study of the evolution of the magnetic and relaxometric properties as a function of metal (Co, Ni) doping in iron oxide nanoparticles. A set of five samples, having the same size and ranging from stoichiometric cobalt ferrite (CoFe 2 O 4) to stoichiometric nickel ferrite (NiFe 2 O 4) with intermediate doping steps, was ad hoc synthesized. Using both DC and AC susceptibility measurements, the evolution of the magnetic anisotropy depending on the doping is qualitatively discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…3B, solid lines). A similar mismatch has previously been observed 26,27 and attributed to one or more physical mechanisms not included in the model itself. On this respect, it should be observed that the RMG model describes systems in the so called motional averaging regime (in short MAR, corresponding to fast motions) while our systems are out of the limit of the MAR regime.…”
Section: H Nmr Relaxometric Characterizationsupporting
confidence: 80%
“…3B, solid lines). A similar mismatch has previously been observed 26,27 and attributed to one or more physical mechanisms not included in the model itself. On this respect, it should be observed that the RMG model describes systems in the so called motional averaging regime (in short MAR, corresponding to fast motions) while our systems are out of the limit of the MAR regime.…”
Section: H Nmr Relaxometric Characterizationsupporting
confidence: 80%
“…[27][28][29] It should be noticed that this model presents serious limits for the exact quantitative estimation of E B , but allows us to grasp its general trend as a function of size, shape, and dispersant. 32 On the other hand, no model able to predict the ZFC curve behavior of interacting MNPs is actually widely accepted in the literature, 30 thus preventing us to use a more refined theory for the E B evaluation. The ZFC data were fitted by using the formula…”
Section: And Ac Magnetic Measurements As a Function Of Temperaturementioning
confidence: 99%
“…The efficiency of such particles for diagnostics has indeed been demonstrated to depend on several magnetic (nature of metal ion, spin topology, magnetic anisotropy), morphological/structural (core diameter, shape, crystallinity degree, coating thickness) and chemical (water exchange dynamics, principally due to coating hydrophilicity, permeability and thickness) parameters [ 21 , 22 , 23 , 24 , 25 , 26 ]. Moreover, a great potential of MNPs relies on their reactive surface, which can be exploited for the anchorage of several molecules with different functionalities.…”
Section: Introductionmentioning
confidence: 99%